PENINGKATAN KEMAMPUAN SISWA MEMAHAMI CIRI KEBAHASAAN TEKS PROSEDUR BERBASIS KEARIFAN LOKAL MELALUI STRATEGI RAUT PADA SISWA SMP WAHID HASYIM KOTA MALANG - Frida Siswiyanti (Universitas Islam Malang, 2025)
Abstract: Procedural text is one of the materials that must be taught in Indonesian language subjects. One important aspect in learning activities about procedural texts is analyzing the linguistic aspects contained in procedural texts. However, learning to analyze linguistic aspects in procedural texts experiences obstacles. Students have difficulty analyzing linguistic features in procedural texts. This is evident from the pretest scores which show that around 39% have not completed (scores below the KKM). Therefore, Classroom Action Research (CAR) was carried out by applying the RAUT learning strategy adapted from genre pedagogy. An increase in completeness was seen after the implementation of cycle I by applying the model. Student learning completeness increased from 39% to 66%. In cycle II, the student completeness level reached 88%. This shows that the 4M learning model supported by effective media and teacher attention is an important factor supporting the success of learning activities.